2022
DOI: 10.1093/migration/mnac027
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination toward migrants during crises

Abstract: How do crises shape native attitudes towards migrants? A common threat could produce an empathy channel among natives, but the perception of competition for scarce economic resources could just as easily spark prejudice through a resentment channel. Totally, 3,400 Colombian citizens were surveyed and randomly primed to consider the economic consequences of COVID-19 before eliciting their attitudes towards Venezuelan migrants. The findings suggest that native attitudes towards migrants are substantially more su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…An implication of this result is that future VR experiences developed to elicit empathy toward migration should consider previous attitudes toward migrants to effectively create empathy. To interpret the results, it is also important to note that this study was conducted after the COVID-19 crisis, and previous research has found that people's perceptions of a crisis (such as the COVID-19 pandemic) significantly affect their attitudes toward migrants [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An implication of this result is that future VR experiences developed to elicit empathy toward migration should consider previous attitudes toward migrants to effectively create empathy. To interpret the results, it is also important to note that this study was conducted after the COVID-19 crisis, and previous research has found that people's perceptions of a crisis (such as the COVID-19 pandemic) significantly affect their attitudes toward migrants [51].…”
Section: Discussionmentioning
confidence: 99%
“…The participants were chosen through intentional sampling, and participation was voluntary. In this study, we chose a sample of university students because previous research has shown that treatments for prosocial behaviors are more effective with people in their impressionable years (18-25 years old) [51]. Students who had experienced a personal or family migration process were excluded in order to reduce the potential biases caused by previous experiences.…”
Section: Participantsmentioning
confidence: 99%
“…Participants were chosen through intentional sampling, and participation was voluntary. In this study, we chose a sample of university students because previous research has shown that treatments of pro-social behaviors are more effective with people in the impressionable years (18-25 years old) [73]. Students who had experienced a personal or family migration process were excluded to reduce potential biases caused by previous experiences.…”
Section: Participantsmentioning
confidence: 99%